Relaksasi Autogenik Terhadap Hemodinamik Pasien di ICU - Supriyanti, Endang; Wahyuningsih, Wahyuningsih; Selowarni, Dati; Yulianti, Ita (LPPM Institut Pendidikan Nusantara Global, 2025)
Critically ill patients experiencing dysfunction in one or more organs are highly dependent on hemodynamic monitoring equipment and Intensive Care Unit (ICU) therapy. Autogenic relaxation is one of the non-pharmacological therapy options that can help stabilize the hemodynamic status of patients because it can provide a relaxing effect, reduce mild to moderate physical and psychological stress and tension, and provide comfort so that hemodynamics become stable. The purpose of this study was to determine the effect of autogenic relaxation on the hemodynamics of patients in the ICU at Permata Medika Hospital in Semarang. This study was a quasi-experimental study with a pre-test and post-test non-equivalent control group design, providing a 10-minute autogenic relaxation intervention twice a day for 2 days to the intervention group. Hemodynamics were measured on the first day before the intervention and on the last day after the intervention. Meanwhile, in the control group, hemodynamic measurements were only taken on the first day and the last day using a bedside monitor and observation sheet. The research population consisted of patients treated in the ICU of Permata Medika Hospital in Semarang, with a sample size of 30 people divided into intervention and control groups. The sampling method was accidental sampling. The data were analyzed using the Mann-Whitney test because the results of the normality test showed that the data were not normally distributed. The results of the study showed p-values for systolic blood pressure of 0.340 and diastolic blood pressure of 0.693, pulse of 0.803, respiration of 0.835, body temperature of 0.815, and oxygen saturation of 0.963, indicating no significant difference in hemodynamic status between the intervention group and the control group. Therefore, it can be concluded that autogenic relaxation has no effect on the hemodynamics of patients in the ICU at Permata Medika Hospital in Semarang. These results are likely due to the small and non-heterogeneous sample size. Therefore, further research with a larger and more heterogeneous sample size is needed.